Occurrence and Antibiotic Resistance of Vibrio parahaemolyticus from Shellfish in Selangor, Malaysia - Letchumanan, Vengadesh; Pusparajah, Priyia; Tan, Loh Teng-Hern; Yin, Wai-Fong; Lee, Learn-Han; Chan, Kok-Gan (Frontiers in Microbiology, 2015)
High consumer demand for shellfish has led to the need for large-scale, reliable shellfish supply through aquaculture or shellfish farming. However, bacterial infections which can spread rapidly among shellfish poses a major threat to this industry. Shellfish farmers therefore often resort to extensive use of antibiotics, both prophylactically and therapeutically, in order to protect their stocks. The extensive use of antibiotics in aquaculture has been postulated to represent a major contributing factor in the rising incidence of antimicrobial resistant pathogenic bacteria in shellfish. This study aimed to investigate the incidence of pathogenic Vibrio parahaemolyticus and determine the antibiotic resistance profile as well as to perform plasmid curing in order to determine the antibiotic resistance mediation. Based on colony morphology, all 450 samples tested were positive for Vibrio spp; however, tox-R assay showed that only 44.4% (200/450) of these were Vibrio parahaemolyticus. Out of these 200 samples, 6.5% (13/200) were trh-positive while none were tdh-positive. Antibiotic resistance was determined for all Vibrio parahaemolyticus identified against 14 commonly used antibiotics and the multiple antibiotic resistance index (MAR) was calculated. The isolates demonstrated high resistance to several antibiotics tested- including second and third-line antibiotics- with 88% resistant to ampicillin, 81% to amikacin ,70.5% to kanamycin, 73% to cefotaxime and 51.5% to ceftazidime. The MAR index ranged from 0.00 to 0.79 with the majority of samples having an index of 0.36 (resistant to 5 antibiotics). Among the 13 trh-positive strains, almost 70% (9/13) demonstrated resistance to 4 or more antibiotics. Plasmid profiling for all Vibrio parahaemolyticus isolates revealed that 86.5% (173/200) contained plasmids - ranging from 1 to 7 plasmids with DNA band sizes ranging from 1.2kb to greater than 10kb. 6/13 of the pathogenic V. pathogenic strains contained plasmid. After plasmid curing, the plasmid containing pathogenic strains isolated in our study have chromosomally mediated ampicillin resistance while the remaining resistance phenotypes are plasmid mediated. Overall, our results indicate that while the incidence of pathogenic Vibrio parahaemolyticus in shellfish in Selangor still appears to be at relatively reassuring levels, antibiotic resistance is a real concern and warrants ongoing surveillance.